A novel multi-attribute decision-making method based on neighborhood approximations and its application. (1st August 2022) - Yu, Bin; Xu, Zeshui; Dai, Jianhua; Yang, Tian
Abstract: To reduce the influence of attribute weight on the result of multi-attribute decision-making (MADM), a new MADM method is proposed for MADM, namely, the Disadvantage and Advantage Neighborhood Environments Comparison. This method determines the ranking of objects by analyzing the ratio of advantage neighborhood sets (environments) to the disadvantage neighborhood sets (environments) of objects. First, the advantage and disadvantage neighborhood sets (environments) of objects are constructed on the basis of the attributes of the objects. The two types of advantage and disadvantage neighborhood approximations are presented, and their related properties are studied. Second, a new MADM method is designed according to the advantages and disadvantages of the objects as a means of overcoming the influence of attribute weight on the decision-making results. Finally, we show the process of the method through calculation and the rationality of our method through the comparative analysis and the consistency analysis. Highlights: The neighborhood sets are constructed on account of the attributes of objects. We use advantage and disadvantage neighborhood sets to analyze the objects. A method is designed to overcome the influence of attribute weights on results. The rationality of our method is shown by comparative and consistency analysis.